Genomics assisted functional characterization of Bacillus velezensis E as a biocontrol and growth promoting bacterium for lily - Li, Bingyu; Wan, Junyi; Sha, Jingjing; Tian, Mengyuan; Wang, Mengchen; Zhang, Xinyuan; Sun, Wei; Mao, Yanrong; Min, Jie; Qin, Yiyuan; Liu, Yuqing; Wang, Wenhe; et al. (Frontiers in Microbiology, 2022)
Lily (Lilium spp.) is one of the most famous ornamental flowers globally. Lily basal rot (also known as root rot or stem rot) and lily gray mold have seriously affected the yield and quality of lily, resulting in huge economic losses. In this study, bacterial strain E was isolated from a continuous lily cropping field. Strain E displayed high control efficiency against lily basal rot and gray mold, caused by Fusarium oxysporum and Botrytis cinerea respectively, and promoted the occurrence of scale bulblets. Strain E displayed strong inhibitory effects against several other plant pathogenic fungi and two pathogenic bacteria in dual culture and disc diffusion assays, respectively. Whole genome sequencing revealed that strain E contained a 3,929,247 bp circular chromosome with 4,056 protein-coding genes and an average GC content of 47.32%. Strain E was classified as Bacillus velezensis using genome-based phylogenetic analysis and average nucleotide identity and digital DNA-DNA hybridization analyses. A total of 86 genes and 13 secondary metabolite biosynthetic gene clusters involved in antifungal and antibacterial activity, plant growth promotion, colonization, nutrient uptake and availability were identified in the genome of strain E. In vitro biochemical assays showed that strain E produced siderophores, proteases, cellulases, biofilms, antifungal and antibacterial substances, and exhibited organic phosphate solubilization and swimming and swarming motility, which were consistent with the results of the genome analysis. Colonization analysis showed that strain E could colonize the root of the lily, but not the leaf. Overall, these results demonstrate that B. velezensis strain E can be used as a potential biofertilizer and biocontrol agent for lily production.